Pectin-based composite film: effect of corn husk fiber concentration on their properties - Bernhardt, Dana Cecilia; Perez, Carolina Daiana; Fissore, Eliana Noemi; De'Nobili, Maria Dolores; Rojas, Ana Maria Luisa (2018)
Considering the polysaccharide composition and 32% of crystallinity of the water insoluble fiber extracted from corn husk (CHF) agricultural residue, its filler performance as water vapor permeability (WVP) and mechanical modifier in edible films based on commercial low methoxyl pectin (LMP) was evaluated (0, 1, 3, 5, 8% concentrations). The 53-μm-CHF carried phenolics and carotenes, and composites showed antioxidant capacity. Homogeneous films with a continuous LMP matrix were obtained. The 5%-CHF composite showed the highest surface contact angle (44°) and tensile strength, without change in elongation, while WVP was decreased in the 3–8% CHF-LMP-films. The latter was ascribed to the CHF-filler crystallinity whereas the improvement in mechanical performance and contact angle was attributed to a CHF-interconnected network formed at 5%-CHF critical concentration. Corn husk residue can be utilized as a source of fibers for material development. Composites with enhanced performance can be an antioxidant strategy at food interfaces.